Retrospective Study of Candida sp. Infection in Intensive Care Unit (ICU) RSPAD Gatot Soebroto - Yuni Setyaningsih; Fajriati Zulfa; Nunuk Nugrohowati; S Agus Waluyo Jati; R Prathama Wiradharma (Faculty of Medicine, Universitas Tadulako, 2026)
Background: An Intensive Care Unit (ICU) provides care for patients with critical conditions requiring monitoring and life-support. ICU patients often have comorbidities, impaired immunity, antibiotic exposure, and invasive devices, increasing susceptibility to opportunistic fungal infections, particularly Candida species. Objective: This study aimed to describe the distribution of Candida species among ICU patients at RSPAD Gatot Soebroto during 2021–2022. Methods: A retrospective observational descriptive study was conducted using total sampling. Secondary data were obtained from medical records and microbiology laboratory reports of ICU patients with confirmed Candida infections. Results: The prevalence of Candida infection in the ICU was 7.19% in 2021 and increased to 8.76% in 2022. Candida albicans was the most common species, accounting for 45.45% of cases in 2021 and rising to 55.76% in 2022. Candida tropicalis was the second most frequent species (30.30% in 2021; 20.00% in 2022), followed by Candida glabrata (13.13% in 2021; 16.97% in 2022). Other species included Candida parapsilosis, Candida krusei, Candida famata, Candida ciferii, and Candida lusitaniae. Positive specimens originated from urine, bronchial, sputum, and blood samples. Conclusion: Candida infections in the ICU were mainly caused by Candida albicans; however, emerging non-albicans Candida species indicate continuous surveillance needs worldwide settings clinically.